Body composition determinants of metabolic phenotypes of obesity in nonobese and obese postmenopausal women. (21st May 2013) - Peppa, Melpomeni; Koliaki, Chrysi; Papaefstathiou, Athanasios; Garoflos, Efstathios; Katsilambros, Nicholas; Raptis, Sotirios A.; Hadjidakis, Dimitrios I.; Dimitriadis, George D.
Abstract : Objective : Although obesity is typically associated with increased cardiovascular risk, a subset of obese individuals display a normal metabolic profile ("metabolically healthy obese, " MHO) and conversely, a subset of nonobese subjects present with obesity‐associated cardiometabolic abnormalities ("metabolically obese nonobese, " MONO). The aim of this cross‐sectional study was to identify the most important body composition determinants of metabolic phenotypes of obesity in nonobese and obese healthy postmenopausal women. Design and Methods : We studied a total of 150 postmenopausal women (age 54 ± 7 years, mean ± 1 SD). Based on a cardiometabolic risk score, nonobese (body mass index [BMI] ≤ 27) and obese women (BMI > 27) were classified into "metabolically healthy" and "unhealthy" phenotypes. Total and regional body composition was assessed with dual‐energy X‐ray absorptiometry (DXA). Results : In both obese and nonobese groups, the "unhealthy" phenotypes were characterized by frequent bodyweight fluctuations, higher biochemical markers of insulin resistance, hepatic steatosis and inflammation, and higher anthropometric and DXA‐derived indices of central adiposity, compared with "healthy" phenotypes. Indices of total adiposity, peripheral fat distribution and lean body mass were not significantly different between "healthy" and "unhealthy" phenotypes. Despite having increased fat mass, MHO women exhibited comparable cardiometabolic parameters with healthy nonobese, and better glucose and lipid levels than MONO. Two DXA‐derived indices, trunk‐to‐legs and abdominal‐to‐gluteofemoral fat ratio were the major independent determinants of the "unhealthy" phenotypes in our cohort. Conclusions : The "metabolically obese phenotype" is associated with bodyweight variability, multiple cardiometabolic abnormalities and an excess of central relative to peripheral fat in postmenopausal women. DXA‐derived centrality ratios can discriminate effectively between metabolic subtypes of obesity in menopause.